2016
DOI: 10.1513/annalsats.201508-495oc
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Resident Training on Communication with Families in the Intensive Care Unit. Resident and Family Outcomes

Abstract: At our institution, an on-site communication training program designed for integration into medical residency programs was associated with strongly positive family member outcomes and significant improvements in residents' perceived skills. This intervention may serve to prepare residents for optimal communications with patients and family members in ICUs and elsewhere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 28 publications
0
51
0
Order By: Relevance
“…Interventions can include training and support to enhance primary palliative care by ICU clinicians. 36,37 …”
Section: Discussionmentioning
confidence: 99%
“…Interventions can include training and support to enhance primary palliative care by ICU clinicians. 36,37 …”
Section: Discussionmentioning
confidence: 99%
“…Another study that showed an improvement in relatives’ perception of the communication skills of participants following a simulation intervention only did so after the participants had attended multiple sessions 27. This highlights a potential benefit in repeat ‘dosing’ of simulation interventions and the limitations of what a single session can achieve 37–39.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the CG-CAHPS questions are indeed the appropriate outcome measure for assessing the impact of house staff’s use of a step-by-step protocol for opening medical interviews is debatable (4,22). However, given the now ubiquitous nature of the CAHPS surveys in the United States, understanding how communication training may or may not impact CAHPS scores in house staff clinics and other teaching services will likely be important moving forward (2) with other measures for assessing the value of training initiatives and giving direct feedback to trainees on communication skills being collected in parallel (15 18,20,23). …”
Section: Discussionmentioning
confidence: 99%